Pengembangan Media dan Bahan Ajar Berupa Video Animasi dan Smart Box pada Materi Fikih di MTs Terpadu Berkah Palangkaraya - Yuliana Yuliana; Miranda Miranda; Devi Hariyani; Reza Maulana Dalimunthe; Abdul Aziz (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
The results of the researcher's interviews with teachers at Mts Terpadu Berkah revealed that the process of implementing IT-based media and teaching materials runs smoothly, but sometimes the facilities and availability of IT media are still lacking and this is what hinders the effectiveness of implementation. In the interview process conducted on one of the teachers of the Fiqh subject in grade VIII of the material of sahwi prostration, prostration of gratitude and prostration of recitation, the teacher stated that students are still difficult in understanding the procedures or movements of prostration sahwi, prostration and prostration of gratitude. This qualitative descriptive approach is one of the research efforts to understand a phenomenon that occurs in the field so that it can be drawn. The data collection in this observation is through an interview process with one of the teachers of the Fiqh subject so that the researcher can know the data data strongly and can be analyzed and then draw conclusions. With the above statement, it proves that almost 100% of grade VIII students are able to understand the material shown through animated videos coupled with audio captions. With the results of the analysis of IT-based media and teaching materials and collaborating with the media and smart box materials, it proves that the effectiveness has reached 100% for students' understanding of the Fiqh subject in grade VIII at the Integrated Blessing Institution of Palangkaraya. From the results of our observations, we produced data that the use of IT-based media achieved the effectiveness of students' understanding of the material almost 100%, this is evidenced by the addition of games from smartboxes that contain data directly identifying the understanding and effectiveness of the use of animated video media by evaluation through games and this is also a solution in the challenge of teachers to the understanding of students in grade VIII MTs integrated blessings to the procedures of the sahwi prostration movement, prostration of Thanksgiving and also prostration of Recitation.